1996
DOI: 10.1002/(sici)1097-0215(19960208)65:4<460::aid-ijc12>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Expression of nma, a novel gene, inversely correlates with the metastatic potential of human melanoma cell lines and xenografts

Abstract: nma, a novel gene, was isolated by using a subtractive hybridization technique in which the gene expression was compared in a panel of human melanoma cell lines with different metastatic potential. nma mRNA expression (I .5 kb) is high in poorly metastatic human melanoma cell lines and xenografts and completely absent in highly metastatic human melanoma cell lines. Fluorescence in situ hybridization combined with the analysis of a panel of human-rodent somatic cell hybrids indicated that the nma gene is locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 3 publications
2
31
0
Order By: Relevance
“…36 Some of the up-regulated genes previously had been correlated with cellular dysplasia and tumor malignancy in several types of cancers. For example, type I sigma receptor 37 and nma, 38 which are transmembrane proteins, are known to be expressed in a variety of human tumor cells. Lipocalin 2, neutrophil-gelatinase-associated lipocalin, is reported to be overexpressed in some carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…36 Some of the up-regulated genes previously had been correlated with cellular dysplasia and tumor malignancy in several types of cancers. For example, type I sigma receptor 37 and nma, 38 which are transmembrane proteins, are known to be expressed in a variety of human tumor cells. Lipocalin 2, neutrophil-gelatinase-associated lipocalin, is reported to be overexpressed in some carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…RNA was size fractionated on 6% polyacrylamide/8 M urea gels, blotted onto Hybond N + filters (Amersham) and hybridized as described previously. 47 Northern blots were washed with 26SSC/1% SDS (three times 20 min at 658C) and analyzed by autoradiography. In case of cell lysates, the total RNA of 0.5610 6 cells was size fractionated.…”
Section: Rna Isolation and Northern Blot Analysismentioning
confidence: 99%
“…In an expression screen for components involved in BMP4 signaling in Xenopus embryos, Onichtchouk et al (1999) identified a gene encoding a transmembrane protein highly related to type-I TGFβ receptors. They named the gene product BAMBI (BMP and activin membrane-bound inhibitor) because it lacked an intracellular kinase domain and its overexpression antagonized BMP and activin signaling in Xenopus embryos (Onichtchouk et al, 1999 (Degen et al, 1996), Zebrafish (Tsang et al, 2000, mouse (Grotewold et al, 2001), and rat (Loveland et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In an expression screen for components involved in BMP4 signaling in Xenopus embryos, Onichtchouk et al (1999) identified a gene encoding a transmembrane protein highly related to type-I TGFβ receptors. They named the gene product BAMBI (BMP and activin membrane-bound inhibitor) because it lacked an intracellular kinase domain and its overexpression antagonized BMP and activin signaling in Xenopus embryos (Onichtchouk et al, 1999 (Degen et al, 1996), Zebrafish (Tsang et al, 2000, mouse (Grotewold et al, 2001), and rat (Loveland et al, 2003).Ectopic expression of Bambi mRNA in Xenopus and zebrafish embryos resulted in phenotypes resembling inhibition of BMP signaling (Onichtchouk et al, 1999;Tsang et al, 2000). In vitro biochemical assays showed that the Bambi protein associated with type-I and type-II BMP/ TGFβ receptor complexes in the presence of ligands, suggesting that Bambi inhibits BMP/ TGFβ signaling by interfering with receptor complex formation or phosphorylation of type-I receptors (Onichtchouk et al, 1999;Tsang et al, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation